CD73: a new immune checkpoint for leukemia treatment - Gao, Huan; Zhang, Tingting; Li, Ke; Li, Xia (Frontiers in Immunology, 2025)
Recent studies on the pathogenesis of leukemia have led to remarkable advances in disease treatment. Numerous studies have shown the potential and viability of immune responses against leukemia. In the classical pathway, this process is often initiated by the upstream activity of CD39, which hydrolyzes extracellular adenosine triphosphate (ATP) and adenosine diphosphate (ADP) to AMP. Subsequently, CD73 acts on AMP to generate adenosine, contributing to an immunosuppressive microenvironment. However, CD73 can also utilize substrates derived from other molecules through the non-canonical NAD+ pathway, specifically via the CD38/CD203a/CD73 axis, further enhancing adenosine production and facilitating immune escape. Targeting CD73 has shown potential in disrupting these immunosuppressive pathways, thereby enhancing anti-leukemic immune responses and improving patient outcomes. Inhibiting CD73 not only reduces the levels of immunosuppressive adenosine but also increases the efficacy of existing immunotherapies, such as PD-1/PD-L1 inhibitors, making it a versatile therapeutic target in leukemia treatment. This review discusses the potential of CD73 as a therapeutic target and emphasizes its unique position in the immune escape mechanism of leukemia. Moreover, this review provides an overview of the current research progress and future trends, emphasizing the clinical significance of targeting CD73 and other potential therapeutic strategies in leukemia.